‘It’s bawdier in Greek’: A.C. Swinburne’s Subversions of the Hellenic Code - Charlotte Ribeyrol (Cahiers Victoriens et Edouardiens)
When Algernon Charles Swinburne was asked in 1872 to make a contribution to Théophile Gautier’s Tombeau, he impressed his French friends, including Hugo or Mallarmé, by sending no fewer than six poems, two in English, two in French, one in Latin and one in Greek. This eloquent polyglossia was both an appropriate tribute to his classically-trained French poetic mentor, as well as a means for Swinburne to show off his multifaceted literary skills. In the 19th century, Latin and Greek were indeed powerful signifiers of elitism on both sides of the Channel, as shown by Swinburne’s erudite use of untranslated Greek words or quotations in many of his essays and poems which were meant to baffle ignorant critics. And yet, this public or rather ‘official’ use of the Hellenic tongue to encode cultural excellence may be contrasted with the poet’s subversive treatment of Greek in his correspondence exploring more personal Sadian fantasies. This dual logos reveals a subtle articulation of the erudite and the erotic—the mysterious ‘corrupt’ ’ἔρωτικ’ satirized in W. H. Mallock’s New Republic (1877). This article therefore proposes to focus on the dichotomy of the Hellenic code, split between the learned and the obscene, between high and potentially low culture, in the writings of the hellenophile Victorian poet, who was equally drawn to the alluring calligraphy of Greek, the language of beauty and formal perfection, as well as to the more fleshly promises suggested by certain Hellenic words and images.